1993
DOI: 10.1007/bf00315353
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetic study and effects on growth hormone secretion in healthy volunteers of the new somatostatin analogue BIM 23014

Abstract: We have studied the pharmacokinetics and the effects of BIM 23,014 (BIM), a new, long-acting octapeptide somatostatin analogue, on basal and stimulated GH secretion in normal men. BIM 250 micrograms sc significantly reduced a GHRH-induced increase in plasma GH. The continuous sc administration of BIM for 24 h dramatically blunted spontaneous GH secretion; 2000 and 3000 micrograms daily reduced GH secretion to a greater extent than 1000 micrograms daily. During these experiments a significant negative correlati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

1994
1994
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 28 publications
0
13
0
Order By: Relevance
“…The somatostatin analogue is encapsulated in a polyactide-polyglycolide copolymer. Previous studies showed that the daily lanreotide dose required to reduce plasma GH levels ranges from 1000 to 2000 mg day-' [26] in acromegalic patients.…”
Section: Productmentioning
confidence: 99%
“…The somatostatin analogue is encapsulated in a polyactide-polyglycolide copolymer. Previous studies showed that the daily lanreotide dose required to reduce plasma GH levels ranges from 1000 to 2000 mg day-' [26] in acromegalic patients.…”
Section: Productmentioning
confidence: 99%
“…The synthetic somatostatin analogues, lanreotide and octreotide, have longer plasma half-lives of 90 and 110 min respectively (8,9). However, multiple daily injections or continuous subcutaneous infusion of these drugs remains a necessity and this detracts from patient acceptability.…”
Section: Introductionmentioning
confidence: 99%
“…The disposition half‐life ranges from 80 to 100 min for both routes of administration, which is more than 30 times that of sst. A similar favorable pharmakokinetic is observed with lanreotide 88. These sst analogs can therefore be administered to patients by subcutaneous route, the most common protocol being two or three subcutaneous injections daily.…”
Section: Somatostatin Analogs In Oncologymentioning
confidence: 67%